Sublime Porte sponsorship of Javanese Muslim students in Ottoman lands (1895-1913 A D): the Ottoman archive documents as a source - Asmahan Mostafa Tawfik Khalil Ahmed; Hassan Ahmed Hassan Abozeed (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the sublime Porte of Javanese Muslims in Ottoman lands during 1849-1915 AD with the Ottoman Empire, during 1849-1916 AD ,which focusing on a side of the Ottoman Javanese relationship that was neglected in Western history So, the study is extrapolating this relationship in an episode of conflict between them on the one side, and the Western countries on the other side, depending on the documents of the Ottoman archives in Istanbul, and analyzing them using the historical research approach, and it contributes to recognizing the Javanese Muslims, and the troubles they tolerated to preserve their Islam and gain their independence, and educating their children. The results of this qualitative study indicate that: despite the weakness it was, and its many problems, which hindered it from carrying out its duty, which was hoped for as a caliphate for the Muslims, in confront of the colonial attacks on the lands of Java, it made great efforts to help the students of Javanese Muslims, and this study recommends increasing International studies and conferences on the history of Javanese Muslims throughout the ages, based on Ottoman and local sources, to confront the fallacies issued by Western sources.